Analisis Tingkat Kedisiplinan Siswa dalam Mengikuti Kegiatan Ekstrakulikuler - Dandi, Mahitsa; Nurhidayat, Nurhidayat (Jurnal Porkes, 2022)
The number of students who are enthusiastic in participating in futsal extracurricular activities at SMA Batik 2 Surakarta has not yet another affective aspect, namely the discipline aspect. So that. The purpose of this study was to analyze the level of student discipline in participating in futsal extracurricular activities at SMA Batik 2 Surakarta. So the number of the population of this study from the data collected was 46 students and the samples taken were class X 20 students, XI 16 students, and XII 10 students at SMA Batik 2 Surakarta, while the sampling technique used total sampling technique. Date collection techniques using observation, questionnaires, and interviews. The type of research used is descriptive research using a quantitative approach. The results of this study indicate that the discipline of SMA Batik 2 Surakarta students in participating in futsal extracurricular activities is very high. This result is shown by the extracurricular questionnaire given who answered strongly agree 65.2%. While the disciplinary questionnaire that chose strongly agree was 52.7%. 46 respondents with the highest frequency, namely 90 or 65.2% chose strongly agree. Meanwhile, the agree category is filled with 45 or 32.6%, the disagree category is filled with 3 or 2.2%, the disagree category is filled with 0 or 0%, and the strongly disagree category is filled with 0 or 0%. And 46 respondents, the highest frequency is strongly agree, selected by respondents as much as 218 or 52.7%, while the frequency of agreeing is chosen by 181 or 43.7%, the frequency of disagreeing is 13 or 3.1%, the frequency of disagreeing is 1 or 0.2% and strongly disagree as much as 1 or 0.2%.